Deposited CrN Layer on SKD61 Substrate using Pulse DC Magnetron Sputtering - Dinh, Thanh Binh; Luu, Thuy Chung; Nguyen, Thi Phuong Mai; Pham, Hong Tuan (Old Journal, 2017)
This paper discusses about the CrN layer coating on SKD61 substrate with pulse DC magnetron sputtering by B30-V type system. The vacuum system has low power pulses, residual stress and pulse frequency varied in the range from 8 kHz to 150 kHz. The result indicates that when increasing the pulse frequency from 8 kHz to 150 kHz, the residual stress decreases significantly (about 4.11 GPa to 0.41 GPa). The surface roughness Ra reduces from 7.1 down to 4.2 µm. The X-ray diffraction (XRD) of CrN coating shows that the film has the strong peak stabilization at (111), (200) and (220). The mechanical properties of coating layers are evaluated by nanohardness and residual stress under the surface (200) was 4.11 GPa in case of frequency pulse 150 kHz.